General Plans of Action of the Educational Inspection of Andalucía, Madrid and Basque Country - Barea Romero, Cristóbal (Avances en Supervisión Educativa, 2016)
A comparative description of the current Action Plans of the Education Inspection of the Junta de Andalucía, the Basque Country and the Community of Madrid is made. It establishes the common and divergent elements, as well as the objectives, contents and main lines of action in the three C.C.AA. The underlying inspection model is briefly evaluated. Finally, we conclude with some of the desirable characteristics in the PGA in the discourse of 21st century inspection.